Предмет: Алгебра,
автор: talynev2011
Запишите выражение в виде многочлена стандартного вида:(3x-7)(2-x)=;(2x-y)(3y-x)=;3x(x-y)-(x+y)(3x-y)=
Ответы
Автор ответа:
0
(3x-7)(2-x)=6x-3x2( в квадраті)-14+7x=-3x2+13x-14
(2x-y)(3y-x) =6xy-2x2-3y2+cut=-2x2-3y2+7xy
3x(x-y)-(x+y)(3x-y)=3x2-3xy-3x2-cut+3xy-y2=-y2-xy
(2x-y)(3y-x) =6xy-2x2-3y2+cut=-2x2-3y2+7xy
3x(x-y)-(x+y)(3x-y)=3x2-3xy-3x2-cut+3xy-y2=-y2-xy
Похожие вопросы
Предмет: Литература,
автор: evgeniakulikova36
Предмет: История,
автор: matvveevayana2010
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: Няшка002